Lanskap linguistik di kelurahan Bahu kota Manado - Makasambe, Jeansi; Pandean, Mariam Lidia Mitty; Ranuntu, Garryn Christian (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
This article aims to identify and describe the phenomena of language variation, categories and functions found in Bahu sub-district, Manado city. This research method uses a qualitative descriptive method. Data collection was carried out using observation, documentation and note-taking methods. This research data is in visual form in the form of images containing language variations of the linguistic landscape in Bahu sub-district, Manado city and this data was taken using a cellphone camera. The results of this research found 39 data. Then eight language variations were found, monolingual, bilingual and multilingual. These language variations include two monolingual variations, namely Indonesian and English. There are four variations of bilingualism found. These variations consist of Indonesian-English, Indonesian-Malay Manado, and Italian-English, and English-Japanese. Furthermore, two multilingual variations were found, namely Indonesian-Melayu Manado-English, Indonesian-Javanese dialect-English-Malay Manado. The category of language sign producers in Bahu sub-district, Manado city consists of top-down and bottom-up categories. There are two functions, which consist of informational and symbolic function.